Normal Macroscopic, Morphological and Morphometric Parameters of the Esophagus of White-Bred Rats - Tursunova Matluba Akhrorovna (Academia Open, 2025)
General Background: The esophagus plays a fundamental role in food transportation and peristaltic coordination within the digestive system, making it a vital subject of anatomical and physiological research. Specific Background: Despite its importance, there is limited quantitative information regarding the normal macroscopic and morphometric characteristics of the esophagus in laboratory rats, particularly in white-bred strains, which are essential for biomedical modeling. Knowledge Gap: Previous studies have focused primarily on pathological changes or chemically induced esophageal alterations, leaving a lack of standardized reference data for healthy specimens. Aims: This study aimed to characterize the normal macroscopic, morphological, and morphometric features of the esophagus in healthy white-bred rats under controlled laboratory conditions. Results: The findings revealed that the esophagus is a non-keratinized stratified squamous structure with progressive thickening of the muscular layers toward the lower segment, indicating adaptive enhancement for peristaltic propulsion. Quantitative measurements provided consistent baseline values across epithelial, submucosal, and muscular layers. Novelty: The study provides one of the most comprehensive baseline datasets for normal esophageal morphology in white-bred rats, bridging a critical gap in comparative and experimental anatomy. Implications: These reference values can serve as essential benchmarks for future pathological, toxicological, and pharmacological studies, improving the precision of experimental models involving the esophagus.Highlight : The study presents normal macroscopic and morphometric parameters of the oesophagus in white-bred rats. Findings highlight gradual thickening of muscular layers indicating adaptive peristaltic function. Results provide baseline data valuable for pathological, pharmacological, and anatomical research. Keywords : Oesophagus, Morphology, Morphometry, Histology, White-Bred Rats